Intervenções promotoras de esperança na saúde mental: revisão integrativa - Costa, Jeremias Rodrigues da (Universidade Federal de São Carlos, 2024)
Hope is essential for mental health, promoting well-being and quality of life, while also reducing depression and anxiety. It plays a fundamental role in fostering resilience when facing adversities. Within the family environment, hope helps individuals cope with negative emotions associated with illness. In the nursing field, hope is of paramount importance in patient care, with the healthcare team playing a key role in fostering hope and recovery within complex health contexts. Objective: To map scientific evidence on hope-promoting interventions carried out by nursing professionals with families in the context of mental health. Method: An integrative literature review study covering a 10-year period (2014–2024). Original articles were sourced from the Virtual Health Library, published in English, Portuguese, and Spanish, freely available online in full-text format. Eligible studies included those employing quantitative, qualitative, mixed-method methodologies, primary studies, systematic reviews, meta-analyses, and meta-syntheses that addressed the review question. The Mendeley software was used for reference management, and the selection process followed the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Results: A total of 54 articles were found, from which a final sample of 4 studies was obtained after the selection process. These analyzed studies highlighted strategies for promoting hope and emotional balance in mental health and family care contexts. The strategies identified include psychosocial support programs, effective communication, and professional attitudes that facilitate relationships with family members. Further interventions involved encouraging positive thinking and therapeutic encounters, such as mutual support groups, hope genograms, and eco-maps that offer emotional support. Conclusion: By implementing these strategies, nurses can promote hope and resilience among family members and caregivers, thereby improving their mental and social well-being.
Interventions promoting hope in mental health: an integrative review
Keywords: Esperança; Enfermagem; Família; Saúde mental; Hope; Nursing; Family; Mental health; CIENCIAS DA SAUDE::ENFERMAGEM::ENFERMAGEM PSIQUIATRICA